Geomorphology, Lithostratigraphy, and Structural Influence on Karst Landscape Evolution in the Selasari Area, Southern West Java - Maheswara, Ahmadani; Barkah, M. Nursiyam; Listiawan, Yudhi; Dwi Hadian, M. Sapari (Journal of Geological Sciences and Applied Geology, 2026)
This study investigates the geomorphological characteristics and geological evolution of the Selasari area, Southern West Java, with emphasis on the interaction between lithostratigraphy, tectonic evolution, and karst landscape development. The objectives are to characterize the geomorphological and lithostratigraphic framework, analyze structural control on landscape development, and reconstruct the geological evolution of the area. An integrated approach combining morphographic, morphometric, morphogenetic, lithostratigraphic, and structural characterization from DEM-based interpretation and field observations was applied. The study area is characterized by karst low hills developed on carbonate-dominated lithologies deposited in a shallow marine environment during the Middle–Late Miocene. Structural analyses suggest a dominant NW–SE orientation that may influence drainage development and valley alignment, possibly associated with tectonic activity related to regional subduction processes along southern Java and subsequent uplift during the Plio–Pleistocene. The integration of geomorphological, lithostratigraphic, and structural evidence suggests that the geological evolution of the study area records a transition from shallow marine carbonate deposition to a tectonically uplifted karst terrain. These findings contribute to a better understanding of karst landscape evolution in the Southern Mountains of Java and highlight the importance of integrated geological approaches for understanding structurally controlled karst systems and supporting geological mapping.